Using Engel Curves to Estimate Purchasing Power Parity. A Case Study of the Computation of the Exchange Rate between the Norwegian krone and the U.S. dollar - Erling Røed Larsen (Statistics Norway, Research Department, 2009)
Standard practice of estimating purchasing power parities (PPP) involves using prices, in domestic currencies, of a common basket of goods and services, then calculating the price-equalizing exchange rate. In this article, I substitute observed consumer behavior for price data. On the assumption that an Engel curve for food reflects material standard of living, I estimate Engel curves for food for the United States and Norway. This allows us to calculate the exchange rate required for re-aligning the two curves, i.e. the incomes needed in the two countries to purchase the same standard of living. Since different relative prices or preferences for food can affect the position and slope of the curves, I also estimate the Engel curves of non-food, for which the effect is opposite. Not only does this provide a band of upper and lower bounds of PPP, it also improves upon the assumption of preference homogeneity underlying conventional PPP-computations. Using Consumer Expenditure (CES) data for 2001, I obtain estimated PPP-levels for the rate of the Norwegian krone (NOK) versus the U.S. dollar (USD) in the 5.38-7.90 range. The average rate 1977-2007 was 6.81 NOK per USD. The conventional estimates of PPP from the World Bank and OECD are 8.84 and 9.18 NOK per USD, respectively.
Keywords: C20; D10; E30; F31; 330; Engel curve; exchange rate; material standard of living; purchasing power parity